PV array connected to the grid with the implementation of MPPT algorithms (INC, P&O and FL Method) - Lagdani, Oumnia; Trihi, Mourad; Bossoufi, Badre (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The purpose of this article is to extract the maximum power point at which the photovoltaic system can operate optimally. The system considered is simulated under different irradiations (between 200 W/m2 and 1000 W/m2), it mainly includes the established models of solar PV and MPPT module, a DC/DC boost converter and a DC/AC converter. The most common MPPT techniques that will be studied are: "Perturbation and Observation" (P&O) method, "Incremental Conductance" (INC) method, and "Fuzzy Logic" (FL) control. Simulation results obtained using MATLAB/Simulink are analyzed and compared to evaluate the performance of each of the three techniques.